Respon Time terhadap Tingkat Kecemasan Pasien di Unit Gawat Darurat : Literature Review - Ekan Faozi; Arief Wahyudi Jadmiko; Dimas Ria Angga Pribadi (Jurnal Siti Rufaidah, 2024)
To prevent disability and even death, the emergency unit must immediately carry out medical action, therefore the need to implement an efficient and effective emergency response time is important in determining whether or not it is necessary to provide medical assistance from the time the patient arrives at the ER until the patient enters the operating room or hospital ward. . The aim of this research is to determine the effect of response time on patient and family anxiety in the emergency unit. The methods used in this secondary research are literature review, article search through the Google Scholar, PubMed, Science Direct, SINTA, and Garuda databases. The results found 7 articles in which there was an influence of response time on patient anxiety in the Emergency Unit and other factors that influenced patient anxiety in the emergency unit included gender, age, education, triage, and the role of nurses. Conclusion: The results of the synthesis of 7 research articles are that response time influences patient anxiety in the emergency unit. Other factor that influence patient and family anxiety when in the Emergency Unit are length of response time, gender, age, education, triage, and the role of the nurse.